Limited insurance within the household: Evidence from a field experiment in Kenya - Jonathan Robinson (University of California, Economics Department, 2008)
This paper presents results from a randomized field experiment to test for the importance of limited commitment (due to incomplete contract enforceability) in explaining intra-household risk sharing arrangements in Kenya. The experiment followed 142 daily income earners and their spouses for 8 weeks. Every week, each individual had a 50% chance of receiving a 150 Kenyan shilling (US 2) income shock (equivalent to about 1.5 days income for men and 1 week's income for women). This paper has 2 main results. First, since the experimental payments are random, they allow for a direct test of allocative Pareto efficiency. I reject efficiency, as male private goods expenditures are sensitive to the receipt of the payment. Second, the experiment varied the level of intra-household correlation in the experimental payments between couples. I find that women send bigger transfers to their husbands when shocks are independent or negatively correlated, a result consistent with the presence of limited commitment. I find no difference in transfers for men, likely because the shocks were too small to cause the limited commitment constraint to bind for them.
Keywords: C93; D13; D61; O12; 330; Familienökonomik; Privater Transfer; Test; Kenia